1984
DOI: 10.1002/1097-0142(19840501)53:9<1918::aid-cncr2820530918>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA content in dimethylhydrazine-induced colonic carcinoma and mucosal dysplasia in rats

Abstract: Mucosal dysplasia and carcinoma infiltrating the submucosal layer were induced in rats with dimethylhydrazine. The nuclear DNA content of the cells was measured, and the correlation between the DNA distribution pattern and histopathologic findings was evaluated. In mild and moderate dysplasias, histograms of the nuclear DNA content showed a narrow range of distribution with a sharp peak in the diploid area. In severe dysplasia, however, there was wide distribution and no peak value; this was reminiscent of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…Daminozide (Alar, N-dimethylaminosuccinamic acid) (1) is a plant growth regulator used mainly with apples (although registered for many other crops) to control flower development, to reduce premature fruit fall, and to improve color development, size, and storage capabilities. Daminozide has been found to be a possible carcinogen in laboratory animals (1) and is known to decompose to N′,N′-dimethylhydrazine (unsymmetricaldimethylhydrazine, UDMH) (2) in apple homogenates submitted to heat treatments (2); UDMH residues, too, have been recognized as potential carcinogens when present in foods (3,4). There is particular concern over potential UDMH residues in apple-derived baby foods because the intake/body weight ratio in children is greater than in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Daminozide (Alar, N-dimethylaminosuccinamic acid) (1) is a plant growth regulator used mainly with apples (although registered for many other crops) to control flower development, to reduce premature fruit fall, and to improve color development, size, and storage capabilities. Daminozide has been found to be a possible carcinogen in laboratory animals (1) and is known to decompose to N′,N′-dimethylhydrazine (unsymmetricaldimethylhydrazine, UDMH) (2) in apple homogenates submitted to heat treatments (2); UDMH residues, too, have been recognized as potential carcinogens when present in foods (3,4). There is particular concern over potential UDMH residues in apple-derived baby foods because the intake/body weight ratio in children is greater than in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on daminozide degradation have shown partial hydrolysis of daminozide to 1,1-dimethylhydrazine (unsymmetrical dimethylhydrazine, UDMH) in apples and apple products that are subsequently boiled (Newsome, 1980;Hurter et al, 1989;Saxton et al, 1989). UDMH itself has been identified as a toxin (Barth et al, 1976; Chevrier and Pfister, 1974) and as a potential carcinogen in studies with laboratory animals, and residues have been recognized as a potential human health risk when present in foods (Kimura et al, 1984;Sakita et al, 1983; Christenson and Luginbyhl, 1975;Roe et al, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Daminozide is possibly carcinogenic (Toth et al 1977) and is known to degrade to UDMH when present in apple homogenate (Newsome, 1980). Residues of UDMH in food are of particular concern because UDMH has been identified not only as a toxin (Chevrier and Pfister 1974;Simpson and Barrow, 1972;Rouganne et al, 1962;Cornish and Hartung, 1969;Barth et al, 1976) but also as a potential carcinogen demonstrated by many studies on laboratory animals (Kimura et al, 1984;Sakita et al, 1983;Scmeltz et al, 1977;Christenson and Luginbyhl, 1975;Roe et al, 1967;Saxton et al, 1989). Despite the fact that Daminozide was prohibited in USA and Canada since 1989, UDMH was found in apples in 1995 (Majumdar et al, 1995).…”
mentioning
confidence: 99%